The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1029/2009tc002446
|View full text |Cite
|
Sign up to set email alerts
|

Ordovician continental margin terranes in the Lachlan Orogen, Australia: Implications for tectonics in an accretionary orogen along the east Gondwana margin

Abstract: Four continental margin turbidite ± black shale terranes of the Lachlan Orogen in the southern Tasmanides of eastern Australia formed in two major systems along the east Gondwana margin and constrain the Ordovician assembly of this accretionary orogen. Key features are the dissimilar stratigraphies of the adjacent Bendigo and Melbourne terranes in the western system; the dissimilar stratigraphies of the adjacent Melbourne and Albury‐Bega terranes that reflect juxtaposition of the two systems during the Middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 105 publications
3
64
0
Order By: Relevance
“…Some recent work has raised questions about the vast Ordovician turbidite fan having formed adjacent to the Delamerian Fold Belt. It has been suggested that the deep-marine Ordovician siliciclastic rocks of the Lachlan Fold Belt formed one or more allochthonous terranes that have been transported along the East Gondwana margin (Baillie, 1985;Glen et al, 2009). Others suggested that long-distance sedimentary transport of sediment from the East -West Gondwana Pan-African collision zones thousands of kilometres away provided an explanation for the detrital U-Pb zircon ages in the Ordovician and other siliciclastic successions (Squire et al, 2006;Maidment et al, 2007;Williams and Pulford, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some recent work has raised questions about the vast Ordovician turbidite fan having formed adjacent to the Delamerian Fold Belt. It has been suggested that the deep-marine Ordovician siliciclastic rocks of the Lachlan Fold Belt formed one or more allochthonous terranes that have been transported along the East Gondwana margin (Baillie, 1985;Glen et al, 2009). Others suggested that long-distance sedimentary transport of sediment from the East -West Gondwana Pan-African collision zones thousands of kilometres away provided an explanation for the detrital U-Pb zircon ages in the Ordovician and other siliciclastic successions (Squire et al, 2006;Maidment et al, 2007;Williams and Pulford, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the Macquarie arc and the surrounding Ordovician quartz turbidites are problematic with several explanations offered including juxtaposition by strike-slip faulting (Glen et al, 2009), island arc rotation and development of adjoining subduction complexes (Fergusson, 2009), and overthrusting of a "passive margin" by an island arc from the east (Aitchison and Buckman, 2012). For the Early Ordovician, a connection between the Gondwana margin and the Macquarie Arc has been argued by Glen et al (2011) who showed that the Mitchell Breccia at the base of the Macquarie Arc succession contains a detrital zircon age pattern similar to that documented for the Ordovician quartz turbidites.…”
Section: Tasmanides Of Southeast Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…: those of the Sunbury Group of Victoria (Glen et al, 2009). One prominent model for the source of these sediments is the so-called "Trans-Gondwanan Supermountain" (TGSM), which is proposed to have developed in Neoproterozoic to Cambrian time during the collision of East and West Gondwana (Squire et al 2006).…”
Section: Comparison With Ordovician Turbidites In the Lachlan Orogenmentioning
confidence: 99%